2019
DOI: 10.3390/rs11121451
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Forest Net Primary Productivity in the Yangtze River Basin and Its Relationship with Climate Change and Human Activities

Abstract: Net Primary Productivity (NPP) is a basis of material and energy flows in terrestrial ecosystems, and it is also an important component in the research on carbon cycle and carbon budget. This paper evaluated the spatial distribution pattern and temporal change trends for forest NPP simulated by the LPJ (Lund-Potsdam-Jena) model and NDVI (normalized difference vegetation index) in the Yangtze River basin from 1982 to 2013. The results revealed that: (1) the spatial distribution of the forest NPP and NDVI in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 46 publications
4
27
0
Order By: Relevance
“…For instance, Gu et al [36] investigated the response of vegetation change to climate change in the Red River basin during 2000-2014 based on the partial correlation and regression analysis. Zhang, et al [37] applied correlation and regression analysis to study vegetation change and its relationship with climate and human factors in the Yangtze River basin from 1982 to 2013. In recent years, quantifying the contributions of climate change and human activities to vegetation change has become a crucial topic of global change.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gu et al [36] investigated the response of vegetation change to climate change in the Red River basin during 2000-2014 based on the partial correlation and regression analysis. Zhang, et al [37] applied correlation and regression analysis to study vegetation change and its relationship with climate and human factors in the Yangtze River basin from 1982 to 2013. In recent years, quantifying the contributions of climate change and human activities to vegetation change has become a crucial topic of global change.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important indicator to monitor the status of vegetation growth. The methods of estimating NPP can be mainly divided into three categories: field measurement, model simulation, and remote sensing estimations [25]. Compared with the other two kinds of methods, the remote sensing estimation method is more suitable for large-scale vegetation research due to its high efficiency and low cost [25].…”
Section: Introductionmentioning
confidence: 99%
“…The methods of estimating NPP can be mainly divided into three categories: field measurement, model simulation, and remote sensing estimations [25]. Compared with the other two kinds of methods, the remote sensing estimation method is more suitable for large-scale vegetation research due to its high efficiency and low cost [25]. Thanks to the rapid development of remote sensing technology, high-resolution remote sensing satellite products have been widely used in vegetation dynamics research on large scales in recent years [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forest vulnerability to climate change is mainly adjudged by changes in the phonological characteristics, tree line shifts, distribution of forest types and productivity (Kumar et al, 2018 and references therein). The NPP has been used to evaluate response of forest ecosystem to climate in many studies (e.g., Yong et al, 2007;Gao et al, 2013;Zhang et al, 2014;Fang et al, 2013;Erşahin et al, 2016;Liu et al, 2018;Gang et al, 2019;Zhang et al, 2019). Zhou et al (2018) reported a substantial decrease in forest NPP in southeastern China in 2009-2010 droughts (from August 2009 to April 2010).…”
Section: Introductionmentioning
confidence: 99%